Clinical safety of a minor eye conditions scheme in England delivered by community optometrists. Issue 1 (20th February 2018) - Konstantakopoulou, Evgenia; Harper, Robert A; Edgar, David F; Larkin, Genevieve; Janikoun, Sarah; Lawrenson, John G
Abstract : Objective: The aim of this study was to monitor the activity and evaluate the clinical safety of a minor eye conditions scheme (MECS) conducted by accredited community optometrists in Lambeth and Lewisham, London. Methods and analysis: Optometrists underwent an accredited training programme, including attendance at hospital eye services (HES) clinics. Patients who satisfied certain inclusion criteria were referred to accredited MECS optometrists by their general practitioners (GPs) or could self-refer. Data were extracted from clinical records. A sample of MECS clinical records was graded to assess the quality of the MECS optometrists' clinical management decisions. Referrals to the HES were assessed by the collaborating ophthalmologists and feedback was provided. Results: A total of 2123 patients (mean age 47 years) were seen over 12 months. Two-thirds of the patients (67.3%) were referred by their GP. The most common reasons for patients needing a MECS assessment were 'red eye' (36.7% of patients), 'painful white eye' (11.1%), 'flashes and floaters' (10.2%); 8.7% of patients had a follow-up appointment. Of the patients seen, 75.1% were retained in the community, 5.7% were referred to their GP and 18.9% were referred to the HES. Of the HES referrals, 49.1% were routine, 22.6% urgent and 28.3% emergency. Of the records reviewed, 94.5% were rated as appropriately managed; 89.2% of the HES referrals were considered appropriate. Conclusion: The findings of this study indicate that optometrists are in a good position to work very safely within the remits of the scheme and to assess risk.